CollaboVR: A Reconfigurable Framework for Creative Collaboration in Virtual Reality - He, Zhenyi; Du, Ruofei; Perlin, Ken (2020 IEEE International Symposium on Mixed and Augmented Reality (ISMAR), 2020)
Writing or sketching on whiteboards is an essential part of collaborative discussions in business meetings, reading groups, design sessions, and interviews. However, prior work in collaborative virtual reality (VR) systems has rarely explored the design space of multi-user layouts and interaction modes with virtual whiteboards. In this paper, we present CollaboVR, a reconfigurable framework for both co-located and geographically dispersed multi-user communication in VR. Our system unleashes users' creativity by sharing freehand drawings, converting 2D sketches into 3D models, and generating procedural animations in real-time. To minimize the computational expense for VR clients, we leverage a cloud architecture in which the computational expensive application (Chalktalk) is hosted directly on the servers, with results being simultaneously streamed to clients. We have explored three custom layouts - integrated, mirrored, and projective - to reduce visual clutter, increase eye contact, or adapt different use cases. To evaluate CollaboVR, we conducted a within-subject user study with 12 participants. Our findings reveal that users appreciate the custom configurations and real-time interactions provided by CollaboVR. We have open sourced CollaboVR at https://github.com/snowymo/CollaboVR to facilitate future research and development of natural user interfaces and real-time collaborative systems in virtual and augmented reality.